The pruned gene encodes the Drosophila serum response factor and regulates cytoplasmic outgrowth during terminal branching of the tracheal system. - Guillemin, K.; Groppe, J.; Ducker, K.; Treisman, R.; Hafen, E.; Affolter, M.; Krasnow, M.A. (Development, 1996)
We identified a Drosophila gene, pruned, that regulates formation of the terminal branches of the tracheal (respiratory) system. These branches arise by extension of long cytoplasmic processes from terminal tracheal cells towards oxygen-starved tissues, followed by formation of a lumen within the processes. The pruned gene is expressed in terminal cells throughout the period of terminal branching. pruned encodes the Drosophila homologue of serum response factor (SRF), which functions with an ETS domain ternary complex factor as a growth-factor-activated transcription complex in mammalian cells. In pruned loss of function mutants, terminal cells fail to extend cytoplasmic projections. A constitutively activated SRF drives formation of extra projections that grow out in an unregulated fashion. An activated ternary complex factor has a similar effect. We propose that the Drosophila SRF functions like mammalian SRF in an inducible transcription complex, and that activation of this complex by signals from target tissues induces expression of genes involved in cytoplasmic outgrowth.